So the problem is asking you to write y + 1 = 6(x+4) in the form Ax+By=C. A lot of this will involve algebra and moving the numbers around until you have it in the right form.
1) Start by distributing 6 to x and 4 on the right using the distributive property.
y + 1 = 6(x+4)
y + 1 = 6x + 6(4)
y + 1 = 6x + 24
2) Move everything with the variables x or y onto the left side using addition or subtraction. Move everything else onto the other side. This means subtracting the 6x from both sides and subtracting 1 from both sides. Simplify:
y + 1 = 6x + 24
y - 6x + 1 = 24
y - 6x = 24 - 1
y - 6x = 23
3) Put your equation in the form Ax+By=C.
y - 6x = 23
-6x + y = 23
-------
Answer: -6x + y = 23
A = -6, B = 1, C = 23